LIVING QURAN MEMBANGUN INFRASTRUKTUR IBU KOTA NEGARA BARU REPUBLIK INDONESIA - Syamsuri . (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2020)
The Living Quran is a study of the Koran as a holy book that is always "alive" to guide humans, in building and managing the universe. Al-Quran is the most noble reading, guiding the reader (reciter ') when carrying out individual, group, or state activities. Al-Quran is a manual book for humans to build infrastructure as the main capital for technological, industrial and economic strength. Building infrastructure in the new capital city of the Republic of Indonesia, begins with zoning in East Kalimantan Province. The launching of the grandbreaking of development, as a prayer asking for grace from Allah SWT, so that work goes according to plan. Munajat is a blessing, in fact it is the living Quran in providing inspiration to project implementers. So that every time you face problems and challenges, there is always a way out (yaj'allahu makhrajan)